Physical abuse in childhood and intimate partner violence in Peruvian women: A population-based survey, 2019 - Vargas-Fernández, Rodrigo (2022)
Intimate partner violence (IPV) is a global health problem and a violation of individual rights. The objective of this study was to assess the association between physical child abuse and current IPV in women of childbearing age in Peru. An analytical cross-sectional analysis of the data from the 2019 Demographic and Family Health Survey was carried out. IPV was constituted by emotional, physical and sexual violence, while physical child abuse was constructed from variables related to physical punishment that women of childbearing age experienced during childhood. Poisson's family generalized linear models were used for the crude and adjusted analyses to determine the association between physical child abuse and IPV. Data from a total of 21,518 women of childbearing age were included. 67.1% of women experienced physical abuse in childhood, while 57.7% experienced intimate partner violence. After adjusting for the characteristics of the woman, the partner or husband, marriage or relationship and the home, it was observed that having experienced physical abuse during childhood increased the probability of experiencing emotional (adjusted prevalence ratio [aPR] 1.15; 95% confidence interval [CI]: 1.09–1.21), physical (aPR 1.33; 95% CI: 1.20–1.47), sexual (aPR 1.57; 95% CI: 1.26–1.96) and any type of violence (aPR 1.15; 95% CI: 1.09–1.21) in adulthood. In conclusion, physical abuse during childhood is a public health issue in Peru. This study shows that women aged 15 to 49 who experienced physical abuse in childhood are more likely to experience intimate partner violence.